Enhancing comigration-ability of Mg2Sn particles with Mg matrix via interphase segregation of Zn - R. Wang; C.F. Fang; J. Chen; A. Liu; C.J. Li; S.B. Mi; M. Yao; Y.M. Wang (Journal of Magnesium and Alloys, 2025)
This study investigates the impact of Zn alloying on the dispersion of the reinforcing particle in Mg2Sn/Mg composites. In the composite, Zn manifests in three distinct forms: Zn segregation layer between MgMg2Sn, the solid solution and the MgZn2 phase. First-principles calculations confirm that the formation of Zn segregation layer decreases the interfacial energy of the MgMg2Sn. Importantly, this segregation layer significantly enhances the comigration capability of Mg2Sn particles with Mg matrix during sintering flow, effectively hindering the agglomeration and coarsening of the nano-sized reinforcing phase. The dense and uniformly distributed nano-sized Mg2Sn significantly increases the activity of non-basal slip, ensuring good elongation of the composite while enhancing strength. It can be concluded that enhancing the comigration-ability of reinforcing particles with the matrix is an effective strategy for achieving controlled dispersion of high-volume reinforcing particles and an excellent combination of strength and ductility in magnesium matrix composites.